Violent video game effects on salivary cortisol, arousal, and aggressive thoughts in children. (May 2017) - Gentile, Douglas A.; Bender, Patrick K.; Anderson, Craig A.
Abstract: An experiment investigated the effects of violent content in video games on two physiological indicators of the fight-or-flight response (cortisol and cardiovascular changes) and on accessibility of aggressive thoughts in children. Participants played a randomly assigned violent or nonviolent video game, rated the game on several dimensions, and did a word completion task. Results showed that the violent video game increased cortisol and (for boys) cardiovascular arousal (relative to baseline) more than did the equally exciting nonviolent game. The violent game also increased the accessibility of aggressive thoughts. The cortisol findings in particular suggest that playing a violent video game may activate the sympathetic nervous system and elicit a fight-or-flight type response in children. Theoretical implications and future research are discussed.